The role of varietal attributes on adoption of improved seed varieties: The case of sorghum in Kenya - Timu, G.A.; Mulwa, R.; Okello, J.; Kamau, M. (Springer, 2014)
This paper examined the effect of variety attributes on adoption of improved sorghum varieties in Kenya. Using data from a random sample of 140 farmers, a multivariate probit was used to identify variety-specific drivers of adoption. The results on the perception of farmers variety attributes showed that improved varieties had desirable production and marketing attributes while the local varieties were perceived to have the best consumption attributes. Evidence further indicated that the major sorghum variety attributes driving rapid adoption are taste, drought tolerance, yield, ease of cooking, and the variety’s ability to fetch a price premium. Early maturity, a major focus of research was found to have no effect on the adoption decision. The findings of the study implied that, while developing improved seed varieties, breeders should also focus on non-yield attributes like taste and ease of cooking to increase adoption and satisfy the multiple needs of the farmers.